Characterization of early defence responses in rust-infected sunflower - Bezuidenhout, Mariette (University of the Free State, 2008)
English: Plants are equipped with a surveillance system which enables the plant to recognize an invading pathogen. After recognition, the stress signal is conveyed throughout the plant cell and subsequent defence responses are activated. Protein kinase genes encode proteins which play important roles in the relay of the initial signal. The aim of this study was to characterise some aspects of the defence response of sunflower upon infection with P. helianthi. One such aspect was the identification of a putative protein kinase gene from the resistant sunflower cultivar. The HaLRD15 gene showed good homology (e-value 7e-151) to a Calcineurin B-like protein kinase (CDPK). The virtual protein encoded by the HaLRD15 gene contained various phosphorylation sites and a MAPK docking site. These sites could lead to the protein being phosphorylated thereby conveying the stress signal throughout the plant cell. Further analyses of HaLRD15 in different sunflower cultivars indicated that the gene was inducible expressed in only one resistant cultivar, even though gene copies were present in all the tested cultivars. This led to the conclusion that HaLRD15 could be essential factor needed in the defence response. Furthermore, an attempt was made to obtain putative disease resistance genes which are differentially expressed in sunflower after infection by using primers specific for the nucleotide binding site of resistance genes. One such gene fragment obtained was NBS6. The polypeptide sequence of NBS6 showed homology to a hypothetical protein containing a DUF26 domain. Further analysis of NBS6 showed that the gene is up-regulated by defence response related chemicals such as MeJA and menadione. Literature have implicated that receptor-like protein kinases containing DUF26, were involved in the defence responses in the plant-pathogen interaction, more specifically in the response of plants upon oxidative stress. As photosynthesis related genes were also differentially expressed, the effect of the leaf rust pathogen on the photosynthetic capacity of both resistant and susceptible cultivars was investigated by using chlorophyll fluorescence. The electron transport rate of the infected resistant plants was shown to be much lower than that of the infected susceptible plants. However the energy dissipated as heat (NPQ) was shown to increase over time in the infected susceptible plants. The expression of various genes such as glutathione S-transferase and the large and small subunit of Rubisco were finally analysed. The infected susceptible plants were shown to have a higher down-regulation of the RbcS gene than the infected resistant plants. The higher electron transport rate of the infected susceptible plants in combination with the low induction levels of RbcS as well as a higher induction of GST during the early intervals, led to the conclusion that the susceptible plants increase the electron transport system to produce higher amounts of reactive oxygen species, thereby leading to the higher induction of GST expression.

Afrikaans: Plante is in staat om potensiële patogene te herken deur middel van ‘n baie effektiewe deteksiesisteem. Dit kan lei tot die aktivering van die plant se verdedigingssisteem. Dit is egter afhanklik van die oordraging van seine vanaf die plasmamembraan van die sel tot in die kern. Proteïen kinases is nou betrokke by die oordraging van sodanige seine. Die doel van die studie was om sekere aspekte van die verdedigingsrespons van sonneblomme na infeksie met P. helianthi te ondersoek. Die eerste was om die rol van `n gekloneerde proteïen kinasegeen, HaLRD15, tydens die verdedigingsrespons te bevestig. Die geen het hoë homologie (e-waarde 0) met `n calcineurin B-tipe protein kinase (CDPK) getoon. Die gekodeerde polipeptied besit verskeie fosforileringsgebiede, asook `n MAPK vashegtingsgebied. Die teenwoordigeheid van die gebiede impliseer dat HaLRD15 betrokke is by seinoordraging aangesien dit self gefosforileer kan word. Die uiting van die geen was in slegs een van die getoetsde kultivars geïnduseer, ten spyte daarvan dat dit in al die kultivars teenwoordig was. Die gevolgtrekking wat dus gemaak was, is dat HaLRD15 `n essensiële komponent van die algemene verdedigingsrespons van sonneblomme kan wees. Tweedens was daar gepoog om weerstandsgene wat differensieël in geïnfekteerde sonneblomme tot uiting kom, te kloneer. Priemstukke spesifiek vir die nukleotiedbindingsgebied is daarvoor gebruik. NBS6 was een van die klone wat vir verdere analiese gekies was. Die gekodeerde polipeptied was homoloog aan `n hipotetiese protein wat `n DUF26 gebied besit het. Die geen se uiting was deur beide MeJA en menadioon wat verdedigingsverwante chemikalieë is, aangeskakel. Uit die literatuur was dit duidelik dat proteïene wat die gebiede besit, betrokke is by die verdedigingsrespons tydens verskeie plant-patogeen interaksies, maar veral tydens oksidatiewe spanning. Laastens is daar ook ondersoek ingestel na die invloed wat die patogeen op die fotosintetiese vermoë van beide vatbare en weerstandbiedende sonneblomme gehad het. Chlorofil-fluoresensie was hiervoor gebruik. Die elektronoordragtempo van die geïnfekteerde weerstandbiedende plante was laer as die van die vatbare kultivar. Laasgenoemde het egter met die verloop van die studie verhoogde hitteverlies (NPQ) getoon. Verder is die uiting van verskillende gene soos GST, RbcL en RbcS ook bepaal. In vergelyking met die geïnfekteerde weerstandbiedende plante, was die uitingsvlakke van RbcS laer in die vatbare plante. Dit, tesame met die verhoogde elektronoordrag, het gelei tot die afleiding dat vatbare plante tydens infeksie die elektronoordragsisteem moontlik eerder vir die produksie van reaktiewe suurstofspesies gebruik. Dit lei dan ook tot die verhoogde uiting van GST soos tydens die studie waargeneem.
Keywords: Puccinia helianthi; Protein kinases; Plant defence; CIPK; DUF26; Chlorophyll lfluorescence; Sunflowers -- Diseases and pests; Sunflowers -- Disease and pest resistance -- Genetic aspects; Rust diseases; Thesis (Ph.D. (Plant Sciences))--University of the Free State, 2008